Invitation to computer science C++ version - Schneider, G. Michael (Thomsom/Course Technology, 2004)
In this best-selling text, Mike Schneider and Judy Gersting unify and lend relevance to the topics of computer science within their proven framework of a six-layer hierarchy of abstractions. The authors begin by showing that computer science is the study of algorithms, which is the central theme of the book, then move up the next five levels of the hierarchy: hardware, virtual machine, software, applications, and ethics. Each layer in the hierarchy builds upon the ideas and concepts presented in earlier chapters. In addition to some motivational applications such as Web page design and interactive graphics, the book covers the fundamental issues of algorithms, hardware design, computer organization, system software, language models, theory of computation, and social and ethical issues of computing. Exposure to these deeper and more complex core ideas introduces students to the richness and beauty of the field and helps them appreciate the principles behind their creation and implementation. While feeling the excitement of computer science, students receive a solid grounding in the central concepts as well as in important uses of computing and information technology.